Clinical practice guidelines for the prevention of childhood obesity: A systematic review of quality and content. (11th July 2022) - Gooey, Michelle; Skouteris, Helen; Betts, Juliana; Hatzikiriakidis, Kostas; Sturgiss, Elizabeth; Bergmeier, Heidi; Bragge, Peter
Summary: Obesity in childhood is a significant global issue, and prevention is key to reducing prevalence. Healthcare providers can play an important role in the prevention of obesity. The aim of this systematic review was to identify and evaluate clinical practice guidelines (CPGs) for preventing childhood obesity with a focus on the role of medical doctors. Peer‐reviewed literature and gray literature sources were searched for CPGs published from 2010 to 2021. Eleven CPGs were identified. Quality was evaluated using the Appraisal of Guidelines for Research and Evaluation Collaboration (AGREE II) instrument; seven CPGs were higher quality and four lower quality. Recommendations within the CPGs covered three main areas: growth monitoring, maintaining a healthy weight, and managing overweight. The importance of involving the whole family and healthy lifestyle behaviors was emphasized. The majority of the CPGs rated poorly in guideline applicability highlighting the need for practical implementation tools. Although our review identified a number of CPGs relevant to the prevention of obesity for doctors working with children and their families, more research is needed to produce high‐quality meaningful and applicable CPGs to maximize uptake, implementation, and ultimately, benefit to children and their families.